THE EFFECTIVENESS OF ETHANOL EXTRACT OF BINAHONG LEAVES ON DIABETIC WOUND HEALING - Anggraeni, Devita; Airin, Claude Mona; Raharjo, Slamet (Universitas Syiah Kuala, 2017)
This research aimed to study the effectiveness of ethanol extract of binahong leaves on blood glucose, insulin, blood chemical profiles (serum glutamic pyruvate transaminase=SGPT, serum glutamic oxaloacetic transaminase=SGOT, ureum, and creatinine), and skin histopathology in diabetic rat. A total of 20 male Wistar rats aged 3 months ( 250 gram) were divided into five groups, with four rats in each group. Group I (non-diabetic control) was injected with 0.1 M sodium citrate buffer, while group II (diabetic control), III, IV, and V were injected with single dose of Streptozotocin (STZ) at dose 40 mg/kg intraperitoneally (IP). One week after the injection, the dorsal skin of the rats were excised. Group I and II were given cream topically and 1% NaCMC orally, group III was given 50% ethanol extract of binahong leaves (EEB) topically and 1% NaCMC orally, group IV was given cream topically and EEB 300 mg/kg orally, and group V was given 50% EEB topically and EEB 300 mg/kg orally. These treatments were continued for 14 days. Blood samples were obtained at the end of study to examine blood glucose, insulin, and blood chemical profiles (SGOT, SGPT, ureum, and creatinine). Examination of skin histopathology and leukocyte count were also done. The result showed that blood glucose, insulin, SGOT, SGPT, and ureum level of diabetic rats given topical or oral EEB did not significantly different from diabetic control group, even though blood glucose, insulin, SGOT, SGPT, and ureum level of diabetic rats given topical and oral EEB were found lower compared to diabetic control group. Administration of EEB 300 mg/kg orally in diabetic rats could lower creatinine level significantly (P0.05). Histopathological examination of dorsal skin of diabetic rats which were given EEB topically showed the decrease of fibroblast proliferation, leukocyte infiltration, and hemorrhage in dermis area. Leukocyte count on skin tissue was significantly lower (P0.05) in diabetic rats given EEB. In conclusion, topical or oral administration of EEB can help healing process in diabetic wound.